A novel α-Fe2O3/AlOOH(γ-Al2O3) nanocatalyst for efficient biodiesel production from waste oil: Kinetic and thermal studies. (November 2020) - Mohamed, Mohamed Mokhatr; Bayoumy, W.A.; El-Faramawy, Hossam; El-Dogdog, Wagdy; Mohamed, Ashraf A.
Abstract: Different α-Fe2 O3 loading (4–12 wt%) doped nanowires AlOOH/γ-Al2 O3 catalysts are synthesized using a deposition hydrothermal technique and thoroughly characterized using XRD, SAED-TEM, FTIR, UV–Vis, N2 sorptiometry and XPS measurements. The 12 wt% α-Fe2 O3 /AlOOH(γ-Al2 O3 ) catalyst presented the highest fatty acid methyl ester (FAME) Yield that comprised of 100% for virgin oil and 94.3% for the waste one, all performed under mild optimized conditions (60 °C, methanol to oil molar ratio = 6:1, 3 wt% catalyst, reaction rate 600 rpm and within 3 h reaction time). It also shows high recyclability without significant loss in activity because of the superior large surface area (323.3 m 2 /g), high number of acid sites (0.45 mmol g −1 ), deep pore volume (0.322 ml/g) and to the exposed active site planes (110) and (214) of α-Fe2 O3 . The kinetic constant (k = 0.016–0.02 min −1 ) and the activation energy (Ea  = 57.4 kJ mol −1 ) of the reaction together with ΔH ‡ (59.4 kJ mol −1 ), ΔG ‡ (+95.9 kJ mol −1 ) and ΔS ‡ (- 0.108 kJ mol −1 ) values elaborate that the reaction is endothermic, non-spontaneous and obey an associative path. The fuel properties derived from cottonseed oil exhibited high quality biodiesel comparable to the international (ASTM) standards. Highlights: α-Fe2 O3 doped AlOOH/γ-Al2 O3 is synthesized using a deposition hydrothermal route. Tranesterification of the virgin cottonseed oil using 12% catalyst gives 100% biodiesel Yield. 12% Fe loading catalyst achieves 94.3% for transesterification of the waste cooking oil. This catalyst gives high recyclability and high-quality fuel characteristics.